Evaluation of polyphenol and antioxidant properties of Blumea balsamifera extract as potential therapeutic for breast cancer - Kamila Fairuz Sarah; Annisa Yuslinda; Rosyadah Nuraini; Hermanto Feri Eko; Widyananda Muhammad Hermawan; Dwijayanti Dinia Rizqi; Widodo Nashi (BIO Web of Conferences)
Blumea balsamifera (Bb) is a plant used as herbal medicine in Southeast Asia, and it has been used due to its antibacterial, antiinflammatory, anticancer, etc. However, there is currently limited evidence that Bb leaf extract from Batu, Indonesia, contains beneficial compounds against breast cancer. Hence, this study evaluates the active compounds in extract and their potential as therapeutic agents for breast cancer. The total phenolic and flavonoid content was determined based on quantified colourimetry analysis followed by DPPH assay to evaluate antioxidant activity and phytochemicals screening in the extract, which was characterised by LC-HRMS analysis. Furthermore, computational methods are used to predict the pharmacological properties of compounds in the extract, particularly against breast cancer. The results showed a total phenolic content of 103.85+1.5 mgGAE/g and a total flavonoid content of 225.99+17.68 mgQE/g, with an antioxidant activity of 255.17+13.11µg/mL. 11 compounds were identified, but only four (Aurantio-obtusin, Isorhamnetin, Quercetin, and Hemiphloin) were computationally analysed. Molecular docking and dynamics simulation indicate that these phytochemicals bind to their target, possibly limiting their activity. Therefore, Bb has potential as a natural product remedy for breast cancer and contributes significantly to our knowledge of the plant by providing essential data for its future development.